Evaluation of in vitro and in vivo adhesion and immunomodulatory effect of Lactobacillus species strains isolated from chickens - Rocha, T. S. [UNESP]; Baptista, Ana Angelita Sampaio [UNESP]; Donato, T. C. [UNESP]; Milbradt, E. L. [UNESP]; Okamoto, Adriano Sakai [UNESP]; Rodrigues, J. C. Z. [UNESP]; Coppola, M. P. [UNESP]; Andreatti Filho, Raphael Lucio [UNESP] (Poultry Science Assoc Inc, 2012)
This study aimed to characterize the in vitro and in vivo adhesion and immunomodulatory effect of Lactobacillus strains isolated from chickens. Lactobacillus samples isolated from 65-wk-old birds were identified by PCR; their adhesion was evaluated in vitro via basement membrane-type cell matrix and in vivo through carboxyfluorescein succinimidyl amino ester staining inoculation in 1-d-old birds and duodenum, jejunum, ileum, and cecum collections at 1, 4, 12, and 24 h after inoculation. The 5 best adhesive samples at the in vitro test formed a pool for total IgA and IgG measurement in sera and intestinal fluid. The birds were divided into groups by inoculation scheme: group 1 was treated with a pool of Lactobacillus spp. at 2-d-old and challenged 1 d later with Salmonella Enteritidis and then treated again with a pool of Lactobacillus spp. at 4 d of age; group 2 was treated with a pool of Lactobacillus spp. at 2 and 4 d of age; group 3 was challenged with Salmonella Enteritidis at 3 d of age; and group 4 was a negative control. Collections were taken at 7, 14, 21, 28, and 35 d after the first inoculation. The results suggest that basement membrane matrix use represents an important technique for triage of samples for subsequent in vivo evaluation and that carboxyfluorescein succinimidyl amino ester staining is efficient for identifying this bacterial characteristic. The Lactobacillus treated groups (1 and 2) presented the highest IgA concentrations at the end of the experiment (12,054.6 and 10,568.4 ng/mL, respectively). The group 2 IgG values in intestinal fluid exceeded those of the other 3 groups (P < 0.05), peaking at 6.419 ng/mL. In most serum collections, the Lactobacillus-treated groups (1 and 2) did not differ significantly in IgG concentrations (P > 0.05), whereas group 3 presented the highest concentration of this antibody. It is concluded that there was greater adhesion of strains in the cecum and an important correlation between in vitro and in vivo results. These results also suggest the immunomodulatory action of Lactobacillus spp. in the chicken.
Keywords: Lactobacillus; in vitro adhesion; in vivo adhesion; immunomodulation chicken